Faktor Ibu dan Praktik Pemberian Makan Balita dengan dan tanpa Malnutrisi: Maternal Factors and Feeding Practices of Children Under Five with and without Malnutrition - Rachma Purwanti; Ayu Rahadiyanti; Dewi Marfu'ah Kurniawati; Hartanti Sandi Wijayanti (Universitas Airlangga, 2025)
Background: Feeding practices are associated with malnutrition. Objectives: To analyze differences in maternal factors and feeding practices of children under five with and without malnutrition. Methods: The research was conducted from March to October 2024 in the city of Semarang. The sample size consisted of 97 subjects (P=0.5; Zα=1.96; d=0.1). Inclusion criteria included mothers as primary caregivers, in good health and not pregnant, and toddlers with no history of recurrent or chronic infectious diseases. The variables studied were maternal factors (maternal age at childbirth, number of children, maternal education level, maternal occupation, family income, maternal nutrition knowledge, and attitudes related to feeding), feeding practices (dietary diversity, consumption of main meals and snacks, variety of cooking methods, feeding responsiveness, and feeding during illness and recovery), and nutritional status of toddlers (normal, wasting-stunting, stunting, wasting, and overweight or obesity). Data were collected through interviews using a structured questionnaire and were analyzed descriptively and bivariately. Results: There were significant differences in child characteristics (low birth weight [LBW] status), maternal characteristics (maternal nutritional status, maternal income, and maternal nutrition knowledge), and feeding practices (frequency of healthy snack consumption, maternal cooking methods, feeding responsiveness, provision of children's preferred foods, and forcing children to finish meals) based on their nutritional status (p-value<0.05). Conclusions: Differences in LBW status, maternal nutritional status, maternal income, maternal nutrition knowledge, frequency of healthy snack consumption, cooking methods, feeding responsiveness, provision of children's preferred foods,coercion to finish meals, and maternal nutrition status were found between mothers with and without children experiencing malnutrition. Prevention of malnutrition among toddlers from at-risk families is necessary, especially through education and assistance to optimize responsive feeding patterns and improve the quality and quantity of nutritional intake.